Rubber compositions and rubber crosslinked products

JP2026166051APending Publication Date: 2026-10-14宝福 裕司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025058762
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0012】 本発明に係るゴム組成物およびゴム架橋物は、優れた耐オゾン耐用年数を有することから、被覆ゴムを必要としない安価で安全且つ安心な積層支承ゴムを実現可能である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166051000001_ABST
    Figure 2026166051000001_ABST
Patent Text Reader

Abstract

To provide a rubber composition and a rubber crosslinked product that have excellent ozone resistance and can provide inexpensive, safe, and reliable laminated bearing rubber without the need for a coating rubber. [Solution] The rubber composition according to the present invention is characterized by containing 5 to 30 parts by weight of carbon black and 3 to 40 parts by weight of a quinoline-based antioxidant per 100 parts by weight of natural rubber containing ethylene propylene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a rubber composition and a crosslinked rubber product.

Background Art

[0002] Conventionally, in bearing devices for structures such as buildings and bridges, sliding bearings with a mechanism for smoothly displacing the structure relative to the foundation, and bearing devices with a mechanism in which laminated rubber is sandwiched between two flanges have been known. In particular, for bridge bearing devices, rubber bearing devices have come to be required since the Great Hanshin Earthquake disaster in 1995. Among them, laminated rubber bearing devices that have vertical load supporting performance and high horizontal force dispersion performance have come into wide use (see Patent Document 1: Japanese Unexamined Patent Application Publication No. 2002-181129).

[0003] On the other hand, during the Great East Japan Earthquake that occurred in 2011, damage to the bearing portions was confirmed in multiple bridges equipped with rubber bearings. One of the causes is that ozone-degraded rubber developed cracks and fractured. In line with the 2017 revision of the Specifications for Highway Bridges, the standards for ozone resistance evaluation of rubber bearings by the three NEXCO companies were reviewed. As a result, rubber bearing bodies with long service life and excellent weather resistance (ozone resistance) have come to be demanded (see Patent Document 2: International Publication No. 2023 / 276994).

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Patent Document 2

Summary of Invention

Problems to be Solved by the Invention

[0005] Furthermore, since the aforementioned rubber bearings could not guarantee ozone resistance, it was necessary to cover them with ethylene propylene diene rubber (EPDM) or chloroprene rubber (CR).

[0006] However, in the case of EPDM and CR, it has been confirmed that ozone can penetrate into the gaps in the coating due to delamination caused by differences in the vulcanization system between the coating and the natural rubber, resulting in cracks in the bearing rubber, which has poor ozone resistance. Therefore, the inventors have diligently researched a rubber that can be used for the rubber bearing body without using the coating rubber itself, while also ensuring ozone resistance and having excellent durability and weather resistance. [Means for solving the problem]

[0007] This invention has been made in view of the above circumstances, and aims to provide a rubber composition and a rubber crosslinked product that do not require a coating rubber and can realize an inexpensive, safe, and reliable laminated bearing rubber.

[0008] The present invention solves the above problem by a solution described below as one embodiment.

[0009] The rubber composition according to the present invention is characterized by containing 5 to 30 parts by weight of carbon black and 3 to 5 parts by weight of a quinoline-based antioxidant per 100 parts by weight of natural rubber containing ethylene propylene.

[0010] In the rubber composition according to the present invention, it is preferable that the ethylene propylene is 21 parts by weight or more per 100 parts by weight of the natural rubber.

[0011] Furthermore, the rubber crosslinked product according to the present invention is characterized in that the rubber composition according to the present invention has been crosslinked. In this specification, the term "rubber crosslinked product" includes rubber products in which the rubber composition has been crosslinked and molded. [Effects of the Invention]

[0012] The rubber composition and rubber crosslinked product according to the present invention have excellent ozone resistance, making it possible to realize an inexpensive, safe, and reliable laminated bearing rubber that does not require a coating rubber. [Brief explanation of the drawing]

[0013] [Figure 1] Figure 1 shows the appearance of the test specimens for Example 1 and Comparative Example 1 after testing in this embodiment. [Modes for carrying out the invention]

[0014] The rubber composition according to the present invention is characterized by containing 50 parts by weight or more of natural rubber and blending the composition and crosslinking material in a total of no more than 200 parts by weight. Furthermore, the composition of natural rubber and ethylene propylene rubber according to the present invention contains carbon black, an adhesion promoter, zinc oxide, an anti-aging agent, a fatty acid, and a vulcanizing agent, but is not limited to these, and may contain any component as long as it does not impair the physical properties of the rubber composition.

[0015] A rubber composition is a composition for manufacturing a rubber crosslinked product. Typically, a crosslinking agent such as a vulcanizing agent for sulfur crosslinking (vulcanization) or a peroxide for peroxide crosslinking (PO crosslinking) is incorporated by the final stage of use. However, this is an optional component for achieving the objectives of the present invention. Therefore, when the present invention is applied to the rubber industry, which is its technical field, the rubber composition according to the present invention can correspond to both the masterbatch (A mixture) before the crosslinking agent is kneaded and the final batch (B mixture) after the crosslinking agent has been kneaded. The embodiments for carrying out the present invention will be described in detail below.

[0016] [Rubber compositions and rubber crosslinked products] The rubber composition according to this embodiment contains 5 to 30 parts by weight of carbon black, 3 to 5 parts by weight of a quinoline-based antioxidant, and 50 parts by weight or more of ethylene propylene rubber per 100 parts by weight of natural rubber. Depending on the combination and content ratio of these components, it is possible to provide an inexpensive, safe, and reliable laminated bearing rubber without the need for a coating rubber, as it has excellent ozone resistance and service life.

[0017] Furthermore, the rubber composition combination according to the present invention exhibits excellent properties as a rubber composition even without the addition of plasticizers. While plasticizers are added to impart flexibility and elasticity to rubber, they have been pointed out as potentially affecting the environment and health. Therefore, the rubber composition of this application also takes environmental and health safety into consideration.

[0018] The materials constituting the rubber composition according to the present invention will be described in detail below.

[0019] First, natural rubber generally refers to rubber obtained by collecting the sap (natural rubber latex) of rubber trees, solidifying it, and drying it. However, in this embodiment, synthetic natural rubber, which has isoprene as its main component and is made from artificially synthesized polyisoprene, is also included. Known brands of natural rubber include SMR (standard Malaysian), SIR (standard Indonesian), and TSR (standard Thai), but TSR is preferred, SIR is more preferred, and SMR is even more preferred.

[0020] Next, while furnace, acetylene, and thermal methods are known for producing carbon black, the acetylene method is preferred, the thermal method is more preferred, and the furnace method is even more preferred.

[0021] Further, the furnace carbon blacks applicable to the present embodiment include SAF (super abrasion furnace black), SAF-HS (super abrasion furnace black-high structure), SAF-LS, ISAF (intermediate super abrasion furnace black), ISAF-HS, ISAF-LS, ISAF-LM, I-ISAF-HS, HAF, HAF-HS, HAF-LS, HAF-LS-SC, MAF, FEF, FEF-LS, HMF, SRF, SRF-HS, SRF-LM, SRF-LS, SPF, GPF, APF, FF, CF, SCF, and ECF.

[0022] Note that carbon black is a fine particulate carbon material added for reinforcing rubber, and in the present embodiment, by containing 5 to 30 parts by weight of carbon black selected under the aforementioned conditions, favorable physical properties with a static elastic modulus G of 0.85 to 1.4 are achieved.

[0023] Next, examples of the antioxidant as an ozone-resistant antioxidant include naphthylamine-based, diphenyldiamine-based, amine-based, quinoline-based, monophenol-based, and polyphenol-based antioxidants, among which monophenol-based or polyphenol-based antioxidants are preferred, naphthylamine-based, diphenyldiamine-based or amine-based antioxidants are more preferred, and quinoline-based antioxidants are even more preferred.

[0024] Further, examples of the quinoline-based antioxidants usable in the present embodiment include Antigen RD-F, Antigen AW, Antigen MW (all manufactured by Sumitomo Chemical), Antage RD, Antage AW (all manufactured by Kawaguchi Chemical), Nocrac 224, Nocrac AW (all manufactured by Ouchi Shinko), Nonflex RD, Nonflex AW (all manufactured by Seiko Chemical), and the like.

[0025] Furthermore, when 3 parts by weight of a quinoline-based antioxidant were included per 100 parts by weight of natural rubber, the surface became viscous after 1,688 hours in an ozone resistance test (explained in the examples), and the initial phenomenon of crack formation was observed. On the other hand, when 5 parts by weight were included, it was confirmed that no cracks occurred even after more than 5,000 hours, demonstrating that ozone resistance and extended service life are achieved by incorporating 3 to 5 parts by weight.

[0026] Next, the content of ethylene propylene rubber is preferably 21 to 50 parts by weight, more preferably 25 to 50 parts by weight, and even more preferably 30 to 50 parts by weight, per 100 parts by weight of natural rubber.

[0027] Furthermore, examples of ethylene propylene rubbers that can be used in this embodiment include EP331, EP342, EP251, EP65, EP35, EP33, EP T8241, EP25, EP24, EP123, EP103AF, EP107F, EP57F / C, EP27, and EP93 (all brands manufactured by ENEOS Corporation). Other examples include EPT0045, EPT2060M, EPT3045, EPT3070, EBT3091, EPT3092M, EPT3110M, EBTX-4010M, EPT4021, EPT4045, EPT4045M, EPT4070, and EPT9090M (all brands manufactured by Mitsui Petrochemical Co., Ltd.).

[0028] Furthermore, while ethylene propylene rubber contributes to improving ozone resistance along with antioxidants, it was confirmed that the effect is insufficient if its content is too low.

[0029] Other fatty acids and fatty acid salts used as processing aids include stearic acid, zinc stearate, ricinoleic acid, palmitic acid, myristic acid, barium stearate, calcium stearate, and magnesium stearate. These processing aids are added to improve productivity.

[0030] Examples of vulcanizing agents used for crosslinking include powdered sulfur, precipitated sulfur, insoluble sulfur, colloidal sulfur, and surface-treated sulfur.

[0031] Furthermore, examples of metal oxides used as rubber vulcanization accelerators include zinc oxide No. 1, zinc oxide No. 2, zinc oxide No. 3, Zinca10, Zinca20 (all manufactured by Sakai Chemical), zinc oxide special grade, zinc oxide No. 1, zinc oxide No. 2, zinc oxide No. 3, activated zinc oxide AZO (all manufactured by Seido Chemical Industry), and activated zinc oxide No. 1, activated zinc oxide No. 2, activated zinc oxide No. 3 (all manufactured by Honjo Chemical). The content of these metal oxides per 100 parts by weight of natural rubber is preferably 1 to 5 parts by weight, more preferably 2 to 5 parts by weight, and even more preferably 3 to 5 parts by weight.

[0032] Examples of tackifiers necessary for bonding the aforementioned rubber compositions or crosslinked rubber products to steel plates include macron resins, phenol terpene resins, and petroleum hydrocarbon resins. These tackifiers are present in amounts of 3 to 5 parts by weight per 100 parts by weight of natural rubber.

[0033] Crosslinking the rubber composition according to this embodiment yields a crosslinked rubber product. The crosslinked rubber product according to this embodiment has excellent ozone resistance and, when used as a laminated bearing body rubber, does not require a coating rubber, eliminating concerns about the coating rubber and the body rubber peeling off, thus enabling the provision of a safe and inexpensive product. Furthermore, the rubber composition and crosslinked rubber product of this application are applicable to molded products such as high-damping rubber, anti-glare materials, and vibration-damping rubber.

[0034] [Method for producing rubber compositions and crosslinked rubber products] Next, the method for producing the rubber composition according to this embodiment involves blending 5 to 30 parts by weight of carbon black, 3 to 5 parts by weight of an anti-aging agent, and 50 parts by weight or more of ethylene propylene rubber with 100 parts by weight of natural rubber.

[0035] Furthermore, the method for manufacturing a crosslinked rubber product according to this embodiment involves crosslinking a rubber composition manufactured by the method for manufacturing a rubber composition according to this embodiment.

[0036] The combination and blending ratio of components, processing aids, additives used for crosslinking, and details of the adhesive for metals in the method for producing the rubber composition according to this embodiment are as described for the rubber composition according to this embodiment. Furthermore, the composition of natural rubber and ethylene propylene rubber according to the present invention contains carbon black, an adhesion promoter, zinc oxide, an anti-aging agent, a fatty acid, and a vulcanizing agent, but is not limited to these, and any other components may be added as long as they do not impair the physical properties of the rubber composition.

[0037] Furthermore, the rubber composition according to the present invention contains 50 parts by weight or more of natural rubber, and the composition and crosslinked material are blended in a total of 200 parts by weight or less.

[0038] Furthermore, the rubber composition can be manufactured by applying the usual rubber composition manufacturing method, provided that the specified mixing ratios of each component are followed. Similarly, the crosslinked rubber product can be manufactured by applying the usual crosslinking method to the manufactured rubber composition. As an example, components including natural rubber, carbon black, ethylene propylene rubber, antioxidants, and other additives are added in a conventional order and kneaded to obtain a so-called masterbatch (A mix) before the addition of crosslinking agents, etc. This masterbatch is storable. For kneading, a kneader such as a Banbury mixer, internal mixer, or kneader, which are commonly used in the rubber industry, the technical field to which this invention belongs, can be used. Next, crosslinking agents (components) such as vulcanizing agents, vulcanization accelerators or vulcanization aids, vulcanization retarders, and peroxides are added to the masterbatch in a conventional order and kneaded to obtain a so-called final batch (B mix) after the addition of crosslinking agents, etc., and dispensed using a roller machine. After that, this can be pressurized and heated to advance crosslinking and molded into the desired shape to obtain a rubber product. In this example, the rubber composition corresponds to the masterbatch (compound A) to the final batch (compound B), and the crosslinked rubber material corresponds to the rubber product. [Examples]

[0039] According to the formulations shown in Table 1 for each example, the components were kneaded using a Banbury mixer: 6D (Kobe Steel, Ltd.) and a kneader: DX75-215 (Nippon Spindle Manufacturing Co., Ltd.) in accordance with conventional methods to produce rubber compositions. The materials used are listed below.

[0040] [Materials used] [Type of ingredient (substance) / Name of ingredient (substance)] Display name in Table 1: Product name (; Remarks) (Manufacturer), however, if the ingredient (substance) name and product name are the same, the product name is omitted. [Natural Rubber] Natural Rubber: RSS (from Malaysia) [Ethylene Propylene Rubber] EPDM: EP-33 (ENEOS Corporation) [Vulcanization aid / Zinc oxide] Zinc oxide (1): Zinc oxide type 1 (Sakai Chemical Industry Co., Ltd.) [Vulcanization aid / zinc oxide] Zinc oxide (2): Activated zinc (Seido Chemical Industry Co., Ltd.) [Anti-aging agent / N-isopropyl-N'-phenyl-p-phenylamine] Quinoline-based anti-aging agent: Nocrack 3C (Ouchi Shinko Chemical Industry Co., Ltd.) [Diphenylamine / N-isopropyl-N'-phenyl-p-phenylamine]diphenyldiamine series: Antige 3C (Kawaguchi Chemical Industry Co., Ltd.) [Reinforcement Agent / Carbon Black] Carbon Black (1): Asahi #80 (Asahi Carbon Co.) [Reinforcement Agent / Carbon Black] Carbon Black (2): Dia Black (Dia Black is a registered trademark) (Mitsubishi Chemical Corporation) [Reinforcement Agent / Carbon Black] Carbon Black (3): Asahi #50 (Asahi Carbon Co.) [Reinforcement Agent / Carbon Black] Carbon Black (4): Asahi #70 (Asahi Carbon Co.) [Processing aid / Stearic acid] Stearic acid: Lunac S-10 (Lunac is a registered trademark) (Kao Corporation) [Tackifier] Sumilight Resin 13349 (Sumitomo Chemical Co., Ltd.) [Vulcanizing agent / Surface treatment sulfur] Sulfur compound: Sulfax PMC (Sulfax is a registered trademark) (Tsurumi Chemical Industries Co., Ltd.) [Vulcanization accelerator / Diphenyl-guanidine] Vulcanization accelerator (1): Noxellar D (DP) (Noxellar is a registered trademark, the same applies hereinafter) (Ouchi Shinko Chemical Industry Co., Ltd.) [Vulcanization accelerator / 2-mercaptobenzothiazole] Vulcanization accelerator (2): Noxellar MP(M) (Ouchi Shinko Chemical Industry Co., Ltd.) [Vulcanization accelerator / N-cyclohexylbenzothiazole-2-sulfenamide] Vulcanization accelerator (2): Noxellar CZ-G (CZ) (Ouchi Shinko Chemical Industry Co., Ltd.)

[0041] [Preparation of test samples] (Ozone resistance test) The rubber composition for each example was placed in a 150mm x 150mm x 2mm mold and crosslinked at 150°C and 15MPa for the appropriate time using a 70t molding machine (Nimei Koki Co., Ltd.).

[0042] Next, using a test piece punching die conforming to JIS K 6251, which is specified in JIS K 6259 for ozone resistance, a dumbbell-shaped No. 1 test piece conforming to the said standard was prepared from the manufactured crosslinked material, with a parallel section length of 40 mm, a parallel section width of 10 mm, and a parallel section thickness of 2 mm.

[0043] [Test Method] (Ozone resistance test) Using ISO 1431 and JIS K 6259:2004 as reference standards for ozone resistance, static and dynamic ozone degradation tests were conducted using an ozone weather meter OMS-LVCP (Suga Test Instruments Co., Ltd.). In the static ozone degradation test, each test specimen marked with a gauge distance of 20 mm was subjected to static elongation with a tensile strain of 80% for more than 5,000 hours in an atmosphere of ozone concentration of 100 ± 10 pphm, temperature of 40 ± 2 °C, and humidity of 65% or less. After that, the ozone concentration was further increased to 200 ± 10 pphm and continued for another 1,000 hours.

[0044] [evaluation] (Ozone resistance test) The presence or absence of breakage in the dumbbell-shaped test specimens was checked. Furthermore, regarding cracks, the test specimens were observed with the naked eye and under a 10x magnifying glass, referring to Annex 1 of JIS K 6259:2004. Specimens that maintained their initial dumbbell shape, had a number of cracks of A or less according to the evaluation criteria of the standard, and could not be confirmed in size were classified as "no cracks detected." On the other hand, specimens that maintained their initial dumbbell shape, had a number of cracks of B or more according to the same evaluation criteria, and could clearly be confirmed in size were classified as "cracks detected." The static ozone degradation test and the dynamic ozone degradation test were then evaluated as follows.

[0045] 80% stretch static ozone degradation test ◎: Observation of the test specimen after 5,000 hours at 100 pphm showed no cracks, and further observation of the test specimen after 408 hours at 200 pphm showed no cracks or fractures. ○: Observation of the specimen after 5,000 hours at 100 pphm revealed no cracks, while observation of the specimen after 408 hours at 200 pphm revealed cracks and fractures. ×: Cracks or fractures were observed in the test specimen after 5,000 hours at 100 pphm.

[0046] [Test Results] Table 1 shows the formulations for each example and the test results for each example.

[0047] [Table 1]

[0048] Examples 1, 2, and 3 demonstrate excellent ozone resistance, as evidenced by the results of an 80% stretch static ozone degradation test. Observation of the test specimens after 5,000 hours at 100 pphm showed no cracks, and observation of the test specimens after 1,000 hours at 200 pphm showed no cracks or breakage.

[0049] In 2019, the three NEXCO companies required a 100-year service life for the laminated bearing body rubber. Therefore, in accordance with JIS K6259-1, it was required that no cracks would occur after 1,512 hours under conditions of static stretching of a No. 1 dumbbell at 80% and a concentration of 1 PPM, and after 408 hours at a concentration of 2 PPM. The evaluation of this application was conducted based on the above tests, and it is presumed that Examples 1, 2, and 3 can guarantee a 100-year ozone resistance service life.

[0050] Furthermore, Figure 1 shows the appearance of the test specimens after testing in Example 1 and Comparative Example 1.

[0051] In the test specimen of Example 1, no deterioration or cracks were observed on the rubber surface, whereas in Comparative Example 1, multiple cracks were observed.

[0052] Looking at the comparative examples, Comparative Example 1, which contained neither a tackifier (phenol terpene resin) nor an antioxidant (quinoline-based), did not perform as well as the example, even though it contained a vulcanization accelerator (2-mercaptobenzothiazole). Similarly, Comparative Example 2, which contained an antioxidant (quinoline-based) but in a relatively small amount of 3 parts by weight and did not contain a tackifier (phenol terpene resin), also did not perform as well as the example. Furthermore, in Comparative Example 3, which contained neither a tackifier (phenol terpene resin) nor an antioxidant (quinoline-based), and which contained a diphenyldiamine-based antioxidant, it did not perform as well as the example.

[0053] Furthermore, regarding the rubber composition related to the example, tests were conducted on the bearing body rubber material according to Table 5-2 of the NEXCO Structural Construction Management Guidelines. The results showed that no cracks occurred even after 5,000 hours under ozone concentration of 100 pphm conditions at 80% elongation at 40°C. The test was further confirmed for 1,000 hours under conditions where the ozone concentration was increased to 2 ppm, for a total of 6,000 hours of testing, but no cracks occurred.

[0054] From the results above, it was confirmed that the rubber composition according to this embodiment has excellent ozone resistance and an estimated service life of 100 years or more, making it possible to provide an inexpensive, safe, and reliable laminated bearing rubber without the need for a coating rubber.

[0055] Furthermore, based on the above results, it is preferable that the rubber composition with the above-described structure contains 5 to 30 parts by weight of carbon black and 3 to 5 parts by weight of a quinoline-based antioxidant per 100 parts by weight of natural rubber containing ethylene propylene. It is also preferable that the amount of ethylene propylene is 21 parts by weight or more per 100 parts by weight of natural rubber.

Claims

1. For 100 parts by weight of natural rubber containing ethylene propylene, Carbon black 5 to 30 parts by weight, and It contains 3 to 5 parts by weight of a quinoline-based antioxidant. A rubber composition characterized by the following.

2. The ethylene propylene is, in proportion to 100 parts by weight of the natural rubber, It must be 21 parts by weight or more. The rubber composition according to claim 1, characterized by the following:

3. A crosslinked rubber product comprising the rubber composition according to claim 1 or claim 2.

Citation Information

Patent Citations

  • Supporting device

    JP2002181129A

  • Rubber composition for rubber bearing body side walls, and rubber bearing body using same

    WO2023276994A1